Diagnostic accuracy and risk stratification of the score for trauma triage in the geriatric and middle-aged among older adults with fall-related injuries - Oluwaseun John Adeyemi; Sanjit Konda; Charles DiMaggio; Corita R. Grudzen; Ashley Pfaff; Garrett Esper; Mauricio Arcila-Mesa; Allison M. Cuthel; JohnRoss Rizzo; Jean-Baptiste Bouillon-Minois; Helen Poracky; Polina Meyman; et al. (PLoS ONE, 2025)
Background Despite fall-related injuries accounting for over two-thirds of older adult trauma injuries, fall-related injuries are more likely to be under-triaged. The Score for Trauma Triage in the Geriatric and Middle-Aged (STTGMA) is an injury risk-triage tool. This study aims to validate STTGMA’s accuracy in predicting fall-related mortality among older adult trauma patients and compare its predictive accuracy with the Geriatric Trauma Outcome Score (GTOS) and the Revised Trauma Score (RTS). Methods Using a retrospective cohort design, we selected 6,458 older adult trauma patients (aged 65 years and older) from a single institutional trauma database (2017–2023). The primary outcome variable was in-hospital death, measured as a binary variable. The primary predictor variable was the STTGMA score, measured as a continuous variable and a four-level categorical variable. The secondary predictor variables were the GTOS and the RTS. We compared the predictive accuracy (95% confidence interval (CI)) of the STTGMA, GTOS, and RTS. We further assessed the relationships between the STTGMA risk categories and time-to-death and hospital length of stay using multivariable time-varying Cox proportional hazard analysis and multivariable quantile regression analysis, respectively. Results A total of 130 patients (2.0%) died during admission, and the median hospital length of stay was 2 days. STTGMA exhibited 84% (95% CI: 77.3–89.8) accuracy in predicting in-hospital fall-related mortality, while the GTOS and RTS both exhibited 71% diagnostic accuracies. Compared to the minimal risk category, older adult trauma patients classified as low, moderate, and high risks each had significantly longer hospital stays and adjusted mortality risks, in a dose-response pattern. Conclusion STTGMA can accurately predict in-hospital mortality and risk-stratify the length of stay and the time to death among older adult trauma patients with fall-related injuries.